Comparative study of photoluminescence properties obtained from SiO2/GaN and Al2O3/GaN structures. (10th July 2019) - Takada, Noriharu; Taoka, Noriyuki; Ohta, Akio; Yamamoto, Taishi; Truyen, Nguyen Xuan; Yamada, Hisashi; Takahashi, Tokio; Ikeda, Mitsuhisa; Makihara, Katsunori; Shimizu, Mitsuaki; Miyazaki, Seiichi
Abstract: Photoluminescence properties of SiO2 /GaN and Al2 O3 /GaN structures formed with plasma-enhanced chemical vapor deposition (PECVD) or atomic layer deposition (ALD) methods were systematically investigated. Intensities related to the band edge (BE) transition for the ALD-SiO2 /GaN and ALD-Al2 O3 /GaN structures significantly decrease compared with the intensity for the GaN surface after a wet-chemical cleaning. The BE intensities have dependences on the temperature of post-deposition annealing (PDA), while they do not achieve the intensity for the wet-cleaned sample even after high-temperature PDA. On the other hand, we found that the BE intensity for the PECVD-SiO2 /GaN structure showed almost no reduction compared with the wet-cleaned sample. These results suggest that the interface between PECVD-SiO2 and GaN is well passivated, and that the PECVD-SiO2 /GaN structure is suitable for future electrical and optical GaN devices.